MITHILA- A GLOBALIZED ART FORM - Thakur, Meenakshi (International Journal of Research -GRANTHAALAYAH, 2017)
India has long been a focal point of art. From the traditional to the contemporary, India is fast developing itself as a key destination for those who love art. India is marked by its rich traditional heritage of Tribal/Folk Arts and Culture. Since the days of remote past, the diversified art and cultural forms generated by the tribal and rural people of India have continued to evince their creative magnificence. Apart from their outstanding brilliance from the perspective of aesthetics, the tribal/folk art and culture forms have played an instrumental role in reinforcing national integrity, crystallizing social solidarity, fortifying communal harmony, intensifying value-system and promoting the elements of humanism among the people of the country. Folk and tribal arts are relatively less exposed forms of narrative Indian art and contain within them a gamut of styles originating from various geographical regions in India. Women in the Mithila region of Bihar in north India have painted colorful auspicious images on the interior walls of their homes on the occasion of domestic rituals since at least the 14th century. This ancient tradition, especially elaborated for marriages, continues today. Madhubani painting or Mithila is a style of Indian painting, practiced in the Mithila region of Bihar state, India, and the adjoining parts of Terai in Nepal. Painting on paper for sale has changed this dramatically. Aside from generating important new family income, individual women have gained local, national, and even international recognition. Artists are being invited to exhibitions across India, and to Europe, the United States, and Japan - no longer as "folk artists," but now as "contemporary artists." Mithila's contemporary arts offer astonishingly vital -- and long overlooked -- depth and diversity, ranging from wondrous elaborations of traditional themes and styles to more experimental depictions of new, topical subject matter.